Comparison in force generation and time of foot contact in four different cutting angles between athletes and nonathletes - Sato, K.; Kryklywec, S.; Cremades, J. G. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to determine the differences in peak active vertical ground reaction force (vGRF) and time of foot contact in four different cutting angles of a closedloop situation between two groups. A total of 10 participants (n=5, athletes, n=5, nonathletes) ran across a force plate to measure peak active vGRF and time of foot contact in four different angles. Data were analyzed using two 2x4 mixed-design ANOVA (p<0.05). Results showed athletes produced higher active vGRF in the shorter time of foot contact, compared to the non-athletes. The result showed a significant interaction with the angles and the participants in the time of foot contact (F(3,24) = 4.48, p<.05). The athletes had overall movement efficiency in the closed-loop condition as compared to the non-athletes.